An evaluation of TOEFL preparation program at ELTI Gramedia using CIPP (context, input, process, and product) model - Fransiska M. Ena Tukan; Nanik Supriani (Journal of English Language and Pedagogy, 2021)
This research focuses to investigate how the context, input, process, and product of the TOEFL Preparation Progam at Lembaga Pendidikan Bahasa Inggris, ELTI Gramedia Yogyakarta contribute to the success of the program. The research applied a qualitative research design and collected the data by online observation, online interview, and online documentation. The researcher used Stufflebeam’s theory of CIPP (Context, Input, Process, and Product) Model to evaluate the TOEFL Preparation Program at ELTI Gramedia. The research participants were the director of ELTI Gramedia, the teachers of the TOEFL Preparation Program, and the students of the TOEFL Preparation Program. Findings showed firstly, in the context evaluation, the objective of the TOEFL Preparation program was relevant and fulfilled the student's needs. The objective of a program was based on need analysis. The need analysis underlay the program objective. The need analysis tended to be on market need.  Secondly, in terms of input evaluation, it was good because all the teachers had good quality in teaching at the TOEFL Preparation class. All of the teachers graduated from the English department. The teachers already had some training before they taught in the class. The facilities in teaching online properly facilitated the students. Thirdly, in the process evaluation, it was not good enough because the online teaching and learning were still not effective. Some students were still passive in the class, although the teacher had explained the material rightly. Sometimes, the bad internet connection made them could not enjoy the class efficiently. In teaching strategy, some of teacher did not apply strategies for doing the TOEFL test. The teachers only asked the students to answer the questions and discussed them. Lastly, in the product evaluation, it was good because the TOEFL Preparation program succeeded in improving the student’s skills. The students had higher TOEFL scores than before. While, the students were not maximal to obtain a good score on the TOEFL test. The higher score of TOEFL is 600 scores.